Non-coding RNA in neural function, disease, and aging - Szafranski, Kirk; Abraham, Karan J.; Mekhail, Karim (Frontiers in Genetics, 2015)
Declining brain and neurobiological function is arguably one of the most common features of human aging. The study of conserved aging processes as well as the characterization of various neurodegenerative diseases using different genetic models such as yeast, fly, mouse, and human systems is uncovering links to non-coding RNAs. These links implicate a variety of RNA-regulatory processes, including microRNA function, paraspeckle formation, RNA-DNA hybrid regulation, nucleolar RNAs and toxic RNA clearance, amongst others. Here we highlight these connections and reveal over-arching themes or questions related to recently appreciated roles of non-coding RNA in neural function and dysfunction across lifespan.